A novel approach to global software development for chartered enterprises. (21st March 2011) - Yao, Qing; Sun, Yuqing; Wang, Haiyang
This paper introduces a novel approach to Global Software Development (GSD) that is suited for chartered virtual enterprises. We study the related key problems, such as construction of knowledge base, modelling of software tasks, distribution and integration of tasks, by presenting a prototype, the Intelligent Platform of Virtual Travel Agency (IPVita). A business process is partitioned into a set of loosely coupled software tasks in IPVita. Two algorithms are proposed, namely task-modelling and service-merging, to distribute and collect these tasks through web service techniques. After integration of these tasks, IPVita could provide a complete business process to customers. We present some applied instances of tasks and perform the experiments to testify our approach.